Murther & walking spirits - Davies, Robertson, 1913-1995. (New York, N.Y. : Penguin Books, 1992)
The editor of a Toronto newspaper finds out about his ancestors in an unusual private Film Festival.
Booklist.
Library Journal Starred.
Wilson's Fiction.
Booklist, December 1995.
Library Journal Starred, October 2009.
Wilson's Fiction, January 1996.
Keywords: Family -- Ontario -- Toronto -- Fiction; Journalists -- Ontario -- Toronto -- Fiction; Family -- Toronto (Ont.) -- Fiction; Journalists -- Fiction; Fantastic fiction